The Influence of Islamic Spiritual Guidance by Increasing Mental Peace for the Elderly in Palembang - Akbar, Muhammad Arief Aidil; Suryati, Suryati; Fitri, Hartika Utami; Tajuddin, Fatjri Nur; Rahayu, Katty Febriliani; Abrori, M. Sayyidul (Grief and Trauma, 2023)
This research is based on the researcher’s observation that several elderly residents in care facilities experience inner unrest, feelings of abandonment by their families, and a perceived lack of familial support in their old age. Heightened emotions and sensitivity often lead to conflicts with fellow residents, while social interactions and awareness of religious practices and closeness to Allah remain limited. The type of research used is quantitative eith experimental methods, while the design is used in this research, namely one group pretest posttest which uses samples as many as 58 elderly people and selected again using a puposive sampling technique with a total of 9 people elderly who ae given treatment. Technique data collection using Likert questionnaires and documentation. Analysis techniques data using the Wilcoxon test. The results of this research show that first, the pretest results for the level of mental calm of the elderly are in the medium category with M = 73.5 While the posttest results are in te high category with M = 76.2 while the results of the analysis using the Wilcoxon test showed Z results score = -2.887. It can be concluded that Islamic spiritual guidance using the dhikr method has a positive impact on improving mental calmness in the elderly.